Experimental investigation of enhanced remediation of contaminated soil using ultrasound effect - Adeyinka, Adegbola; Dare, A.A.; Popoola, D.S.; Saka, H.A.; Afolabi, A.O. (International Journal of Engineering and Technology, 2014)
In the development of an effective ground remediation method, there has been significant research focusing on the technique of enhancing soil-flushing method The soil flushing method enhanced by ultrasonic waves is a new technique that is potentially an effective method for in situ remediation of the ground contaminated by NAPL hydrocarbons. The research work investigated the effectiveness of sonication in the soil flushing method for a range of conditions involving treatment time, hydraulic gradient and the discharge velocity. The experimental investigation of the study was conducted using the inbuilt ultrasonic generator (NEE 555 timer stable multi-vibrator) and soil flushing apparatus to remove the contaminant from the soils. The test result indicated that the rate of the contaminant extraction increased considerably with increasing sonication time up to 120seconds with 34% contaminant removed without sonication and 64.05% contaminant removed with sonication and started decreasing at the level where cavitation occurred. Increasing the sonication time also increase the contaminant removal up to the level where cavitation occurs. The effectiveness of sonication decreases with hydraulic gradient but eventually becomes constant under higher flow rates and also is highly related with the discharge velocity. Results obtained showed that sonication can enhance pollutant removal. Keywords: Soil-Flushing Method, NAPL Hydrocarbons, Sonication, Soil Remediation, Cavitation.